Nanostructured back reflectors produced using polystyrene assisted lithography for enhanced light trapping in silicon thin film solar cells - Li, Zeyu (2020)
We study light trapping in hydrogenated amorphous silicon thin film solar cells fabricated by plasma-enhanced chemical vapor deposition on various nanostructured back reflectors. The back reflectors are patterned using polystyrene assisted lithography. We have investigated the correlation between the back reflector optical properties and the corresponding solar cell performance. We have introduced double size polystyrene sphere patterned back reflectors and have provided experimental evidence for improved light trapping performance compared to single size polystyrene sphere patterned back reflectors. We have achieved high performing nanostructured amorphous silicon solar cells with an initial power conversion efficiency of 7.53% and over 20% enhancement of the short-circuit current compared with the reference flat solar cell.